Technical and vocational education and training video’s move analysis lecture content phase - Izzat Rahim, Muhamad; Shamsudin, Sarimah (Opción, 2019)
This study aims to fill the gap by investigating the rhetorical structure of the Technical and Vocational Education and Training (TVET) video lecture content phase. Move and step models by Lee and Ebrahimi were used to analyze five TVET video lectures by Malaysian Polytechnics. It was found that the TVET video lecture content phase normally consists of two moves and four steps. Both moves were considered obligatory. Moreover, the order of steps was found to vary in each of the video lectures. In conclusion, by examining more video lecture styles, the knowledge of video lectures’ rhetorical structure could be enhanced.